A brief emotion regulation training in children and adolescents with obesity: A feasibility study. Issue 4 (July 2022) - Boelens, Elisa; Braet, Caroline; Debeuf, Taaike; Wante, Laura; Volkaert, Brenda; Verbeken, Sandra
Abstract: Background: Recent studies emphasize the role of emotion dysregulation as an underlying mechanism initiating and maintaining emotional eating in obesity. Since multidisciplinary obesity treatment (MOT) does not directly address emotion regulation (ER), the current study aimed to investigate the feasibility of an ER training in children and adolescents with obesity on top of MOT. Feasibility was evaluated multi-informant on relevant parameters e.g. practicability, satisfaction, change in affect and homework compliance. Methods: Participants ( N = 50, M_age = 12.26, 60.7 % girls) with obesity received a brief ER training and were assigned to one out of three conditions to learn one specific ER strategy (i.e., Cognitive reappraisal, Distraction or Acceptance). Afterwards the ER strategy was further trained by a homework assignment during 5 consecutive days. Children and adolescents, trainers and as well as the educators of the treatment center completed a feasibility questionnaire. Results: The training was positively evaluated by different informants for 11 out of 19 feasibility criteria. Only one implementation barrier was reported regarding homework compliance. Furthermore, some important considerations could be taken into account e.g. session length and motivation. Conclusions: Reports suggest that, with some modifications, it is feasible to implement an ER training on top of MOT. In addition, future training protocols should focus on other essential components of ER (e.g., emotional awareness, emotional flexibility).